The Harp and the Eagle : Irish-American Volunteers and the Union Army, 1861-1865. - Ural, Susannah J. (NYU Press, 2006)
On the eve of the Civil War, the Irish were one of America's largest ethnic groups, and approximately 150,000 fought for the Union. Analyzing letters and diaries written by soldiers and civilians; military, church, and diplomatic records; and community newspapers, Susannah Ural Bruce significantly expands the story of Irish-American Catholics in the Civil War, and reveals a complex picture of those who fought for the Union. While the population was diverse, many Irish Americans had dual loyalties to the U.S. and Ireland, which influenced their decisions to volunteer, fight, or end their milita.